Process optimization for the production of fish gelatin nanoparticles - Subara, Deni; Jaswir, Irwandi; Alkhatib, Ma'an Fahmi Rashid; Noorbatcha, Ibrahim Ali (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM)""", 2017)
Animal proteins have become an useful source for producing gelatin nanoparticles, due to its application in cosmetics and therapeutics. Gelatin nanoparticle (GNP) is an excellent biodegradable and biocompatible material. Due to its chemical modification potential gelatin nanoparticles are very promising in carrier system for drug delivery. Most of the commercials gelatin are derived from mammalian sources, such as porcine and bovine. Fish gelatin has become a good alternative resource for GNPs production in view of the various religious, safety and economic reasons. In this present work, the tilapia fish gelatin was used as a raw material for the production gelatin nanoparticles via modified two-step desolvation method. In this process, obtaining high molecular weight (HMW) fraction content of fish gelatin is very crucial for the preparation of stable and small size GNPs. Hence the present study was carried out to assess the various formulation parameters in the first step in the two-step desolvation method to produce fish gelatin nanoparticles (FGNPs). The nanoparticles formed were characterized for mean size and size distribution, while the morphology of the particles was evaluated by field emission scanning electron microscope (FESEM). The size of fish gelatin nanoparticles was found to be 254±11 nm which is suitable for drug delivery. The study indicated that a high fraction of HMW in precipitate at the first step desolvation could be obtained by using gelatin concentration 9%, temperature 45°C, centrifugation speed at 12000 x g, and centrifugation time was 5 min. It showed that this method is efficient compared to conventional method.